Demonstration of Virus in Groundwater after Effluent Discharge onto Soil - Wellings, Flora Mae (1975)
The survival of virus present in secondary effluents discharged into a cypress dome was studied. Isolations were made from concentrates of water drawn from 10-foot (304.80 cm) deep wells. Data presented show vertical and lateral virus movement as well as survival within the dome for 28 days during a period of heavy rains when no effluent was being applied. Due to the inefficiency of virus concentration procedures, it is proposed that much of the virus present was probably not demonstrated. A rapid, relatively inexpensive concentration technique for sewage influents and effluents is discussed.